Preventive justice: Exploring the coercive power of community protection notices to tackle anti-social behaviour - Heap, Vicky (Punishment & society, 2022)
Community Protection Notices (CPNs) are civil preventive orders used in England and Wales to prevent and/or require specific behaviour by an individual or organisation, where existing conduct has a ‘detrimental impact on the quality of life of those in the locality’. Breach of the notice results in a £100 fine under a Fixed Penalty Notice or a possible criminal conviction. To date, CPNs have tackled an array of perceived anti-social behaviours, ranging from rough sleeping to overgrown gardens. Using Ashworth and Zedner’s preventive justice as an analytical framework, our research qualitatively explores recipients’ experiences of this new tool for the first time. The findings highlight how the operationalisation of CPNs extends the coercive power of the state, with a range of negative consequences relating to the concepts of disproportionality, due process and accountability. We also offer three empirically-grounded recommendations for reforming CPN practices.